A Clinicopathological Study of 24 Cases of DFSP - Miyako Kachi; Atsumori Hamahata; Kohei Oashi; Hisato Konoeda; Miho Kirita; Masashi Ishikawa; Hirotaka Koyanagi; Hiroyuki Sakurai (Journal of Plastic and Reconstructive Surgery)
Objectives: Dermatofibrosarcoma protuberans (DFSP) usually arises in the dermis and spreads to the underlying subcutaneous tissue (cutaneous DFSP). However, it rarely appears in the subcutaneous tissue (subcutaneous DFSP). This study aimed to retrospectively analyze the clinicopathological features of patients with the subcutaneous dermatofibrosarcoma protuberans and compare them to those of cutaneous dermatofibrosarcoma protuberans. Methods: A total of 24 patients with dermatofibrosarcoma protuberans who underwent surgical excision at our institution between 1991 and 2022 were included in this study. Results: The tumors were located on the trunk in 18 patients (75%), upper extremity in 2 (8%), and lower extremity in 4 (17%). The median tumor diameter was 4.35 cm. A total of 18 patients underwent surgical resection before arriving at our hospital, 16 of whom had positive surgical margins. At our institution, the tumors were radically resected with a median surgical margin of 2 cm, following which reconstructive surgery was performed in 17 patients (70%). Fibrosarcomatous changes were observed in five patients (21%). Excluding four recurrent cases, the remaining 18 (90%) and 2 (10%) patients were diagnosed with cutaneous dermatofibrosarcoma protuberans and subcutaneous dermatofibrosarcoma protuberans, respectively. The median follow-up period was 5 years. There were no cases of metastasis or recurrence. Conclusions: When subcutaneous dermatofibrosarcoma protuberans appears as a subcutaneous nodule, it is frequently misdiagnosed and improperly treated with unplanned excision owing to the absence of typical skin surface changes. Dermatofibrosarcoma protuberans is locally aggressive regardless of the depth of the principal lesion, and appropriate initial surgical excision with an adequate surgical margin is crucial for definitive treatment.